"Fitting in" and "opting out": exploring how law students self-select law firm employers. Issue 2 (3rd April 2018) - Rowan, Eleanor; Vaughan, Steven
ABSTRACT: In this paper we draw on interviews with 15 law students at the University of Birmingham in the UK to explore the extent to which law students critically self-evaluate themselves against their perceptions of the preferences of elite law firms. While our conclusions are necessarily tentative, we show how some law students "opt out" of applying to certain law firms where they perceive there is no fit between themselves and that law firm. Equally, our data also shows that some students recognise that, despite not having a supplementary fit with a firm (i.e. they can see that they do not "match" that firm's current crop of lawyers or what they think is the firm's culture), they realise that they can instead be a complementary fit for the firm, and hence realise that their potential to add something "new" to the law firm (by way of increasing diversity) can secure them a vacation scheme placement or a training contract. Finally, a proportion of students play "the numbers game" and despite determining a law firm "misfit", still proceed to apply to as many law firms as possible as they thought that more applications meant a higher chance of success.